Penerapan Media Pembelajaran Wordwall untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas II SDN 14 Cakranegara - Nurfitasari, Nurfitasari; Karmajaya, I Wayan Agus; Satiadi, Dadi; Aryanthi, G Ayu (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve learning motivation among second-grade students at SDN 14 Cakranegara through the implementation of Wordwall as a learning medium. The research employed a qualitative descriptive method, combining qualitative and quantitative data analysis. This study was conducted as a Classroom Action Research (CAR) involving 32 students as research subjects. The findings revealed that in the first cycle, the average score of learning outcomes using Wordwall media reached 64%, categorized as moderate achievement. Meanwhile, in the second cycle, the average score increased to 86%, categorized as very good achievement. Therefore, it can be concluded that the use of Wordwall as an interactive learning medium can effectively enhance students’ learning motivation, particularly in learning question sentence material among second-grade students at SDN 14 Cakranegara.